Transcriptome-wide N6-methyladenosine (m6A) profiling of compatible and incompatible responses reveals a nonhost resistance-specific m6A modification involved in soybean–soybean cyst nematode interaction - Qianqian Shi; Xue Han; Xinhao Zhang; Jie Zhang; Qi Fu; Chen Liang; Fangmeng Duan; Honghai Zhao; Wenwen Song (Journal of Integrative Agriculture, 2025)
Soybean cyst nematode (SCN, Heterodera glycines) is a devastating pathogen that infects soybean (Glycine max L. Merrill) and disrupts soybean production worldwide. SCN infection upregulates or downregulates the expression of multiple genes in soybean. However, the regulatory mechanisms that underlie these changes in gene expression remain largely unexplored. N6-methyladenosine (m6A) methylation, one of the most prevalent mRNA modifications, contributes to transcriptional reprogramming during plant responses to pathogen infection. Nevertheless, the role of m6A methylation in establishing compatible and incompatible soybean responses to SCN has not previously been studied. Here, we performed transcriptome-wide m6A profiling of soybean roots infected with virulent and avirulent populations of SCN. Compared with the compatible response, the incompatible response was associated with higher global m6A methylation levels, as well as more differentially modified m6A peaks (DMPs) and differentially expressed genes (DEGs). A total of 133 and 194 genes showed significant differences in both transcriptional expression and m6A methylation levels in compatible and incompatible interactions; the most significantly enriched gene ontology terms associated with these genes were plant–pathogen interaction (compatible) and folate biosynthesis (incompatible). Our findings demonstrate that the m6A methylation profiles of compatible and incompatible soybean responses are distinct and provide new insights into the regulatory mechanism underlying soybean response to SCN at the post-transcriptional modification level, which will be valuable for improving the SCN-resistant breeding.